Vaginal microbiota and HPV clearance: A longitudinal study - Shi, Wenpei; Zhu, Haiyan; Yuan, Lei; Chen, Xiaoyue; Huang, Xiaojie; Wang, Kai; Li, Zhen (Frontiers in Oncology, 2022)
Although vaginal microbiota (VM) may interact with human papillomavirus (HPV) infection and clearance, longitudinal data remains very limited. We aimed to investigate the association between VM at baseline and the clearance of high-risk HPV (HR-HPV) infection within 12 months. Cervical swabs were collected at diagnosis from 85 patients with HR-HPV infection and histologically confirmed cervical lesions, including cervicitis, low-grade squamous intraepithelial lesion (LSIL) and high-grade squamous intraepithelial lesion (HSIL). Microbiome analysis was performed using 16S rRNA gene sequencing. Among the 73 women included in the analyses, HPV clearance was observed in 58.9% of the patients within 12 months. No significant difference was observed between the HPV-cleared and the HPV-uncleared groups regarding age, disease stage, HPV subtype, VM community state types and VM diversity (alpha- and beta-). Women with the depletion of Enterococcus ASV_62 and enrichment in L.iners at baseline were less likely to have HPV clearance at month 12. Further analysis revealed a significant negative association between high abundance of L.iners and HPV clearance in patients who received non-operative treatment (OR=3.94, P=0.041), but not in those who received operative treatment (OR=1.86, P=0.660). Our findings provide new evidence for the potential role of VM in the persistent HR-HPV infections.